(untitled) (Research, Society and Development, 2021)
This study aims to describe the repair through a clinical case of a diffuse and extensive periapical lesion with suggestive diagnosis of chronic periapical abscess. Anamnesis and clinical examination were performed. Based on the correct indication for endodontic treatment, coronary opening and subsequent cervical preparation were performed with GattesGlidden drills, and K-Files type manual instruments were performed in the cervico-medial preparation. Subsequently, intracanal medication based on calcium hydroxide was introduced. After preparing the root canal, the patient underwent intracanal medication consisting of calcium hydroxide. After 15 days, the absence of the sensitivity referred to at the beginning of therapy was verified and, therefore, the canal system was filled with the active lateral condensation technique together with AH-Plus cement. It was verified by radiographic images during the treatment performed, that during the consultations there was a reduction in the diameter of the periapical lesion. This reduction was caused by the intracanal medication, which was renewed every month for a period of six months in order to disinfect the root canal and repair the periapical bone destruction. Therefore, the clinical and radiographic follow-up, after a period of six months of intracanal medication, found the repair of the periapical lesion.